THE EFFECTS OF THE AUTHORITARIAN PARENTING TOWARD STRESS AND SELF-ESTEEM OF TEENS - Dwi Rahmah Fitriani (Universitas Muhammadiyah Kalimantan Timur, 2019)
Adolescence is a period of development and a period of adjustment for adult life and a period of stress and stress is a time of turmoil and pressure. At this time, there was a shift in the role of peers who began to